PENGARUH MACAM PUPUK ORGANIK PADAT DAN INTERVAL PEMBERIAN PUPUK ORGANIK CAIR PADA PERTUMBUHAN DAN HASIL CABAI RAWIT - Daryanti; Tyas Soemarah K.D; Muharram Indrawan; Teguh Supriyadi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Cayenne pepper was a vegetable needed in the daily consumption of people in Indonesia. Efforts to increase the production of cayenne pepper include fertilization. The purpose of this study was to determine the effect of various kinds of organic fertilizer and the interval of liquid organic fertilizer on the growth and yield of cayenne pepper. This study used polybags in plastic houses, from January to May 2019 in Bangsri Village, Karangpandan District, Karanganyar Regency with a height of 450 MASL with Grumosol soil types. This research used a factorial method with the basic design of a Completely Randomized Design (CRD) consisting of 2 treatment factors and is repeated 3 times. The first factor was the type of organic fertilizer (M) consisting of 3 levels, M0 = Soil without organic fertilizer (control), M1 = Soil and Blotong Fertilizer (ratio 1: 1), M2 = Petroganic Soil and Fertilizer (ratio 1: 1 ). The second factor was the interval of adduction liquid organic fertilizer (P) consisting of 3 levels, P0 = Without the adduction of POC (liquid organic fertilizer) (control), P1 = adduction POC every 7 days, P2 = adduction POC every 14 days. The use of organic blotong or Petroganik fertilizer mixed with soil with a ratio of 1: 1 accompanied by the administration of POC Nasa every 14 days produces the highest number and weight of fruit.